County-Level School Sex Education Policy: A Single State Analysis of the Association with Adolescent Birth and Sexually Transmitted Infections. Issue 4 (2nd October 2022) - Zori, Gaia; Foti, Steven; Hart, Mark
Abstract: Substantial evidence supports comprehensive sex education programs as effective means of promoting adolescent sexual health, but evidence on the effect of state-level sex education policy is inconclusive. Multiple states in the U.S. afford local authority in school policy, and existing literature calls for investigation of the impact of local interpretation and implementation of sex education policy. This study is the first to assess the association between stated county policy and select adolescent sexual health outcomes. In this single state multivariate analysis, stated county policy was not significantly associated with adolescent birth or sexually transmitted infections. The incongruity of evidence between the impacts of sex education programs and policies on teen birth and STIs in Florida suggests that implementation of policy and delivery of sex education at the district or school level may not align with stated county policy and may be a critical mediating factor, confirming an area of essential future research in sex education.